Rapamycin as a potential treatment for succinate dehydrogenase deficiency. Issue 2 (February 2019) - Fan, Frances; Sam, Rheba; Ryan, Emma; Alvarado, Katherine; Villa-Cuesta, Eugenia
Abstract: Drosophila melanogaster is a powerful model to study mitochondrial respiratory chain defects, particularly succinate dehydrogenase (SDH) deficiency. Mutations in sdh genes cause degenerative disorders and often lead to death. Therapies for such pathologies are based on a combination of vitamins and dietary supplements, and are rarely effective. In Drosophila, mutations in several of the genes encoding SDH resemble the pathology of SDH deficiency in humans, enabling the Drosophila model to be used in finding treatments for this condition. Here we show that exposure to the drug rapamycin improves the survival of sdh mutant strains, the activity of SDH and the impaired climbing associated with sdh mutations. However, the production of reactive oxygen species, the oxygen consumption of isolated mitochondria and the resistance to hyperoxia were minimally affected. Our results contribute to the current research seeking a treatment for mitochondrial disease.